Knockout of cytochrome P450 3A yields new mouse models for understanding xenobiotic metabolism - van Herwaarden, Antonius E.; Wagenaar, Els; van der Kruijssen, Cornelia M.M.; van Waterschoot, Robert A.B.; Smit, Johan W.; Song, Ji-Ying; van der Valk, Martin A.; van Tellingen, Olaf; van der Hoorn, José W.A.; Rosing, Hilde; Beijnen, Jos H.; Schinkel, Alfred H. (The Journal of clinical investigation, 2007)
Cytochrome P450 3A (CYP3A) enzymes constitute an important detoxification system that contributes to primary metabolism of more than half of all prescribed medications. To investigate the physiological and pharmacological roles of CYP3A, we generated Cyp3a-knockout (Cyp3a-/-) mice lacking all functional Cyp3a genes. Cyp3a-/- mice were viable, fertile, and without marked physiological abnormalities. However, these mice exhibited severely impaired detoxification capacity when exposed to the chemotherapeutic agent docetaxel, displaying higher exposure levels in response to both oral and intravenous administration. These mice also demonstrated increased sensitivity to docetaxel toxicity, suggesting a primary role for Cyp3a in xenobiotic detoxification. To determine the relative importance of intestinal versus hepatic Cyp3a in first-pass metabolism, we generated transgenic Cyp3a-/- mice expressing human CYP3A4 in either the intestine or the liver. Expression of CYP3A4 in the intestine dramatically decreased absorption of docetaxel into the bloodstream, while hepatic expression aided systemic docetaxel clearance. These results suggest that CYP3A expression determines impairment of drug absorption and efficient systemic clearance in a tissue-specific manner. The genetic models used in this study provide powerful tools to further study CYP3A-mediated xenobiotic metabolism, as well as interactions between CYP3A and other detoxification systems.